2008
DOI: 10.1007/s11430-007-0145-2
|View full text |Cite
|
Sign up to set email alerts
|

Two pedogenic models for paleoclimatic records of magnetic susceptibility from Chinese and Siberian loess

Abstract: The magnetic susceptibility (MS) of Chinese loess showing a general proportional relationship to pedogenic grade has been widely recognized and used for reconstruction of paleoclimate by Quaternary scientists. The in-situ pedogenic enhancement of ferrimagnetic content is normally believed to be the main reason for the increase of susceptibility in soil units. However, this pattern of high magnetic susceptibility in palaeosols, and low values in loess, are not replicated in some loess deposits. Siberian loess d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 34 publications
4
39
0
Order By: Relevance
“…Intermittent reduction is required for the formation of the ferrimagnets. Constant oxidation or reduction favors formation and accumulation of non-ferrimagnets [1, [17][18][19][20]41,73]. The wet reducing conditions in NLK resulted in destruction of ferrimagnets and the formation of non-ferrimagnets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intermittent reduction is required for the formation of the ferrimagnets. Constant oxidation or reduction favors formation and accumulation of non-ferrimagnets [1, [17][18][19][20]41,73]. The wet reducing conditions in NLK resulted in destruction of ferrimagnets and the formation of non-ferrimagnets.…”
Section: Discussionmentioning
confidence: 99%
“…In south Siberia, all paleosols, including S0, usually display low susceptibility. This can be explained by the local climate, which causes very moist conditions in the soils [20]. However, during glacial periods, the climate was conjectured to be drier, resulting in relatively oxidizing conditions and preservation of ferrimagnets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ms (T) curves show that all samples have a rapid loss of magnetization near 580°C and that the magnetization of samples taken from the desert zone drops to zero (Figure 4), indicating magnetite is the dominant mineral in these samples. According to the different characteristics of the Ms (T) curves (Figure 4), samples can be divided into three categories: (1) desert samples, for which the magnetization in the cooling curve is slightly greater than that in the heating curve, implying that weakly magnetic materials, such as iron sulfides or other paramagnetic minerals, are converted to strongly magnetic magnetite as a result of oxidation during heating [19,20], (2) loessic sand and loess samples between 2100 and 3300 m, for which the magnetization in the cooling curve is less than that in the heating curve, which is probably due to thermally unstable maghemite minerals converting to hematite, resulting in a loss of magnetization [19,20], and (3) loess samples above 3300 m, for which the magnetization in the cooling curve is much greater (more than double) than that in the heating curve and all heating curves have a clear "hump" at around 500°C. These observations indicate that the types and contents of weakly magnetic minerals differ greatly from those of desert samples [20].…”
Section: Temperature Dependence Of Saturation Magnetizationmentioning
confidence: 99%
“…For example, higher χ during glacial periods and *Corresponding author (email: fangxm@itpcas.ac.cn) lower χ during interglacial periods have been observed in the cases of Alaska loess and Siberia loess. The wind-vigor model [15][16][17][18] and pedogenic model [19,20] have been proposed to explain the complicated correlation. In addition, many studies have shown that coarse aeolian magnetic minerals also affect χ, especially in the loess-paleosol sequence adjacent to the desert edge [21,22].…”
mentioning
confidence: 99%